Adipose Tissue in Persons With HIV Is Enriched for CD4+ T Effector Memory and T Effector Memory RA+ Cells, Which Show Higher CD69 Expression and CD57, CX3CR1, GPR56 Co-expression With Increasing Glucose Intolerance - Wanjalla, Celestine N.; McDonnell, Wyatt J.; Barnett, Louise; Simmons, Joshua D.; Furch, Briana D.; Lima, Morgan C.; Woodward, Beverly O.; Fan, Run; Fei, Ye; Baker, Paxton G.; Ram, Ramesh; Pilkinton, Mark A.; et al. (Frontiers in Immunology, 2019)
Chronic T cell activation and accelerated immune senescence are hallmarks of HIV infection, which may contribute to the increased risk of cardiometabolic diseases in people living with HIV (PLWH). T lymphocytes play a central role in modulating adipose tissue inflammation and, by extension, adipocyte energy storage and release. Here, we assessed the CD4+ and CD8+ T cell profiles in the subcutaneous adipose tissue (SAT) and blood of non-diabetic (n=9; fasting blood glucose [FBG]<100mg/dL), pre-diabetic (n=8; FBG=100-125 mg/dL) and diabetic (n=9; FBG>=126mg/dL) PLWH, in addition to non- and pre-diabetic, HIV-negative controls (n=8). SAT was collected by liposuction and T cells were extracted by collagenase digestion. The proportion of naïve (TNai) CD45RO-CCR7+, effector memory (TEM) CD45RO+CCR7−, central memory (TCM) CD45RO+CCR7+, and effector memory revertant RA+(TEMRA) CD45RO-CCR7− CD4+ and CD8+ T cells were measured by flow cytometry. CD4+ and CD8+ TEM and TEMRA were significantly enriched in SAT of PLWH compared to blood. The proportions of SAT CD4+ and CD8+ memory subsets were similar across metabolic status categories in the PLWH, but CD4+ T cell expression of the CD69 early-activation and tissue residence marker, particularly on TEM cells, increased with progressive glucose intolerance. Use of t-distributed Stochastic Neighbor Embedding (t-SNE) identified a separate group of predominantly CD69 lo TEM and TEMRA cells co-expressing CD57+ CX3CR1+ GPR56+, which were significantly greater in diabetics compared to that in non-diabetics. Expression of the CX3CR1 and GPR56 markers may indicate these TEM and TEMRA cells may have anti-viral specificity. Compared to HIV-negative controls, SAT from PLWH had an increased CD8:CD4 ratio, but the distribution of CD4+ and CD8+ memory subsets was similar irrespective of HIV status. Finally, whole adipose tissue from PLWH with similar glucose tolerance had significantly higher expression of TLR2, TLR8, and multiple chemokines potentially relevant to immune cell homing compared to HIV-negative controls.